Characterization of variable weathered rock profiles by using DPR - A. Viana da Fonseca (2007)
: The highly variable nature of the deeply weathered Porto granite has been posing significant challenges in thegeotechnical design due to the nature of the rock mass when its several class qualities are hard to differentiate. The identificationof geotechnical patterns in weathered rock profiles from conventional borehole investigations is common and ideal but rathertime consuming. Drilling Parameter Recordings (DPR) has been pointed out as a complementary alternative to site investigation.A series of boreholes, where classical exploration techniques were confronted with drilling parametric monitoring, have beenused to develop protocols between indices coming out from this practical and increasingly reliable technique.This paper presents some results from the study developed in this geotechnical ambient, by comparing compound parametersderived from the DPR recorded variable with conventional site investigation results and indices. It is the purpose of this research,developed in collaboration of the industry, to enable this technique to be more confiable in its common use in these formations